A new denoising approach for the removal of impulse noise from color images and video sequences - Rajamani, Argumugam (Image analysis and stereology, 2012)
In this paper a novel Lone Diagonal Sorting (LDS) algorithm for denoising color images and videos co-rrupted with salt and pepper noise is proposed. The proposed lone diagonal sorting algorithm uses diagonal sorting alone for denoising of impulse noise. The algorithm has been implemented and tested for various color images and video signals and appreciable performance in terms of PSNR, MSE and SSIM is obtained. Our algorithm has been compared with other standard algorithms. A drastic improvement in the computational time has been achieved without compromising much on the visual quality after reconstruction.
Keywords: color image; obdelava slik; peak signal to noise ratio; barvna slika; video posnetek; video sequence; signal; šum